Oral SARS-CoV-2 Spike Protein Recombinant Yeast Candidate Prompts Specific Antibody and Gut Microbiota Reconstruction in Mice - Zhang, Lilin; Yao, Lan; Guo, Yanyu; Li, Xiaoyang; Ma, Li; Sun, Ruiqi; Han, Xueqing; Liu, Jing; Huang, Jinhai (Frontiers in Microbiology, 2022)
A recent study showed that patients with COVID-19 have gastrointestinal symptoms and intestinal flora dysbiosis. Yeast probiotics shape the gut microbiome and improve immune homeostasis. Here, an oral candidate of yeast-derived spike protein receptor-binding domain and fusion peptide displayed on the surface of the yeast cell wall was generated. The toxicity and immune efficacy of oral administration were further performed in ICR mice. No significant difference in body weights, viscera index, and other side effects were detected in the oral-treated group. The detectable RBD-specific IgG and IgA of SRAR-CoV-2 and more complex microbiota were detected from oral administration mice compared with those of the control group. Interestingly, the recombinant yeast was identified in female fetal of the high-dose group. These results revealed that the displaying yeast could fulfill the agent-driven immunoregulation and gut microbiome reconstitution. The findings will shed light on new dimensions against severe acute respiratory syndrome coronavirus 2 infection with the synergistic oral agents as promising noninvasive immunization and restoring gut flora.